Adaptation of the Sexuality Scale for Women with Gynecologic Cancer for Turkish Patients - Çigdem Marangoz; Ayten Demir; Eda Özge Yazgan (Elsevier, 2019)
Objective: Diagnosis and treatment of gynecologic cancers can have a negative impact on sexuality. Identification of sexual problems and concerns is key to enable appropriate management. Therefore, there is a need for a valid and reliable instrument for evaluating the sexuality of patients. This study aimed to adapt the sexuality scale for women with gynecologic cancer for Turkish patients with gynecologic cancer. Methods: A cross-sectional study of 150 volunteer patients with gynecologic cancer was undertaken in Turkey. The patients completed a semi-structured demographic data form and the sexuality scale for women with gynecologic cancer. We assessed the reliability, language accuracy, and content and construct validities of the Turkish version of the scale. Results: Exploratory and confirmatory factor analyses showed that the scale had four factors. In the exploratory factor analysis, seven items were discarded from the scale because their load values were <0.3. In the confirmatory factor analysis, the coefficients were higher than 0.3. The total Cronbach's α was 0.72. Conclusions: The sexuality scale for women with gynecologic cancer (Turkish version) is a valid and reliable instrument for evaluating the sexuality of Turkish patients with gynecologic cancer.